Analysis of Genetic Distance and Similarity in Some Radish Cultivars (Raphanus sativus L.) by Random Amplified Polymorphic DNA (RAPD) Markers - A. K. H. Al-Tufaili (Journal of Global Pharma Technology, 2016)
The random amplified polymorphic DNA (RAPD) assay is a useful method for to Detection Genetic Distance and Similarity among cultivars. In the present study, The DNA of the five Radish genotypes were screened with 5 primers generated reproducible and easily storable RAPD profiles with a number of amplified DNA fragments ranging from 9 to 12. The number of polymorphic ranged from 5 to 9 with an average reached 7.4 fragments ̸ primers with the polymorphic percentage ranged from 41.66%to 90%. The number of monomorphic ranged from 0 to 5 and was total of the monomorphic 10 with an average reached 2 fragments ̸ primers with the monomorphic percentage was 0% to 41.66%. A maximum genetic distance value was obtained in Local white radish and white radish Hybrid F1 reached 0.662. While a minimum genetic distance value was seen between Local red radish and Local white radish reached 0.458. The least genetic similarity was between the two cultivars Local red radish and Local white radish 40%. This study shows that the genetic diversity among radish cultivars can be used to improve plant growth, especially medical active compounds production in addition to increasing the plant yield and improve the quality. Keywords: Radish, Genetic Diversity, Molecular marker, RAPD.